Reducing preventable maternal and neonatal deaths: policy, practice and evidence-based pathways to achieve universal health targets - R., Usha Rani; K. S., Ragini; R., Hemavathi; Usha, Chakali; Revathy, V.; Abi Rami, M.; Katiyar, Jyoti; Kalyani, B.; Umar, Mohammed; Kavitha, Gadhi; N. R., Deepa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Preventable maternal and neonatal deaths remain a major global health challenge despite decades of progress and the availability of effective, evidence-based interventions. This review synthesizes current knowledge on policies, clinical practices, and system-level strategies essential for achieving international targets under the sustainable development goals. Evidence from global analyses demonstrates that most maternal deaths arise from postpartum hemorrhage, hypertensive disorders, sepsis, and obstructed labor, while neonatal mortality is primarily driven by preterm birth complications, intrapartum asphyxia, and infections. High-impact interventions including antenatal corticosteroids, active management of the third stage of labor, magnesium sulfate therapy, essential newborn care, Kangaroo Mother Care, and neonatal resuscitation significantly reduce mortality when implemented with fidelity. However, gaps persist in coverage, workforce capacity, facility readiness, referral pathways, respectful maternity care, and community engagement. Health system constraints, including inadequate staffing, poor-quality intrapartum monitoring, limited equipment availability, and social barriers such as gender inequity, further impede progress. Successful country examples highlight the importance of integrated policies, universal health coverage, strong midwifery systems, maternal and perinatal death surveillance and response (MPDSR), and sustained quality-improvement cycles. Digital health innovations, when appropriately supported, improve risk detection, protocol adherence, and accountability. This review underscores that reducing preventable deaths requires not isolated interventions but coordinated, multisectoral strategies spanning clinical, community, and policy domains. Achieving global targets demands strengthening health systems, addressing sociocultural barriers, and ensuring every woman and newborn receives timely, respectful, high-quality care across the continuum.